1. Bộ Y tế. Quyết định ban hành Hướng dẫn về phương pháp đo lường sự hài lòng của người dân đối với dịch vụ y tế công giai đoạn 2024–2030. Hà Nội: Bộ Y tế; 2024. 2. Bộ Y tế. Chỉ thị số 03/CT-BYT ngày 01/4/2013 về việc tăng cường các giải pháp thực hiện t (Vietnam Journal of Community Medicine, 2026)
Background: Patient satisfaction is an important indicator reflecting the quality of healthcare services, in which communication and behavior of healthcare workers play a key role, especially in outpatient care.Objective: To assess the level of satisfaction and factors associated with outpatient satisfaction regarding communication and behavior of healthcare workers. Methods: A cross-sectional descriptive study was conducted on 220 outpatients. Data were collected using a structured questionnaire and analyzed using appropriate medical statistical methods. Results: The proportion of patients who were very satisfied and satisfied accounted for 91.4%, of which 63.7% were very satisfied. Factors significantly associated with patient satisfaction included gender (female: 87.1% vs. male: 73.9%; p
Keywords: Satisfaction, communication behavior, healthcare workers, outpatients.